Diversity and utilization of medicinal plants in Borabue District, Maha Sarakham Province, Northeastern Thailand - WIRA THIPTHAMRONGSAP; SURAPON SAENSOUK; PIYAPORN SAENSOUK (Society for Indonesian Biodiversity, 2025)
Abstract. Thipthamrongsap W, Saensouk S, Saensouk P. 2025. Diversity and utilization of medicinal plants in Borabue District, Maha Sarakham Province, Northeastern Thailand. Biodiversitas 26: 3040-3046. This study provides foundational information for further research and offers conservation status for medicinal plants in Borabue District, Maha Sarakham Province, Northeastern Thailand to ensure continued species richness and sustainable use. The research aimed to document ethnobotanical knowledge and diversity of medicinal plants in two villages, Khok Suea Thao and Khi Lek, Maha Sarakham Province. Ethnobotanical data were interviewed from 30 local informants using semi-structured interviews. A total of 46 medicinal plant species were identified, belonging to 43 genera and 23 families. The Fabaceae family exhibited the highest diversity (9 species), followed by Malvaceae (4 species), while Menispermaceae, Poaceae, and Rubiaceae had three species each. The most frequently used plant part was the roots (27%), followed by leaves (22%), fruits (20%), and stems (14%). Decoction was the most common method of preparation (65%), underscoring the importance of traditional processing techniques. Based on Use Value (UV), the most culturally significant species were Curcuma longa (0.93), Citrus hystrix (0.90), and Chromolaena odorata (0.90). Medicinal plants were used to treat nine ailments across six disease categories, with musculoskeletal disorders showing the highest Informant Agreement Ratio (IAR: 0.97). Of the documented plants, 35 species (61.70%) had a fidelity level of 100%, particularly in treatments focused on restoring and balancing bodily elements. One species, Xylia xylocarpa is listed as Vulnerable based on IUCN criteria. This study contributes valuable data for the conservation of traditional knowledge and plant biodiversity. It emphasizes the importance of preserving ethnomedicinal practices, which are at risk of disappearing due to modernization. The findings support the sustainable development of herbal medicine, promote local economic opportunities through value-added local herbal products, and enhance public health initiatives at both local and national levels.